Multidisciplinary medical identification of a French king's head (Henri IV). (14th December 2010) - Charlier, Philippe; Huynh-Charlier, Isabelle; Poupon, Joël; Keyser, Christine; Lancelot, Eloïse; Favier, Dominique; Vignal, Jean-Noël; Sorel, Philippe; Chaillot, Pierre F; Boano, Rosa; Grilletto, Renato; Delacourte, Sylvaine; et al.
Abstract : Philippe Charlier and a multidisciplinary team explain how they confirmed an embalmed head to be that of the French king Henry IV using a combination of anthropological, paleopathological, radiological, forensic, and genetic techniques